Whole genomic analysis uncovers high genetic diversity of rifampicin-resistant Mycobacterium tuberculosis strains in Botswana - Mogashoa, Tuelo; Loubser, Johannes; Choga, Ontlametse T.; Ngom, Justice Tresor; Choga, Wonderful T.; Mbulawa, Mpaphi B.; Molefi, Tuduetso; Stephen, One; Makhondo, Topo; Seru, Kedumetse; Motshosi, Patience; Zuze, Boitumelo; et al. (Frontiers in Microbiology, 2025)
BackgroundThe emergence of drug-resistant Mycobacterium tuberculosis (M. tb) strains remains a threat to tuberculosis (TB) prevention and care. Understanding the drug resistance profiles of circulating strains is crucial for effective TB control. This study aimed to describe the genetic diversity of rifampicin-resistant M. tb strains circulating in Botswana using whole genome sequencing (WGS).MethodsThis study included 202 stored M. tb isolates from people diagnosed with rifampicin-resistant TB (RR-TB) between January 2016 and June 2023. Genomic DNA was extracted using the cetyltrimethylammonium bromide (CTAB) method. Library preparation was performed using the Illumina DNA prep kit following the manufacturer's instructions. Sequencing was done on Illumina NextSeq2000. TBProfiler software was used to identify known M. tb lineages and drug resistance profiles. Statistical analyses were performed on STATA version 18.ResultsWGS analysis revealed multidrug resistance (57.9%: 95% CI; 50.7–64.8), Pre-XDR (16.8%, 95% CI: 11.9–22.7), RR-TB (20.2%: 95% CI: 14.98–26.5), and HR-TB (0.5%, 95% CI; 0.01–2.7). We identified a high genetic diversity with three predominant lineages: lineage 4 (60.9%, 95% CI; 53.8–67.7), lineage 1 (22.8%: 95% CI; 17.2–29.2), and lineage 2 (13.9%, 95% CI: 9.4–19.4). The most frequently observed drug resistance mutations for rifampicin, isoniazid, ethambutol, streptomycin, pyrazinamide, and fluoroquinolones were rpoB S450L (28.6%), katG S315T (60.5%), embA_c.-29_-28delCT, embB Q497R (31.7%), rrs_n.517C>T (47.1%), pncA_c.375_389delCGATGAGGTCGATGT (36.0%) and gyrA A90V (79.4%), respectively. No bedaquiline and delamanid resistance-associated mutations were detected.ConclusionsThis study highlights the high genetic diversity of M. tb strains, with a predominance of lineage 4 among people with RR-TB in Botswana. It provides valuable insights into the genetic diversity of rifampicin-resistant M. tb strains circulating in Botswana.